Observasi Penerimaan Sosial Berbasis Aplikasi Realitas Tertambah di Bamboo Bar Sanur - Prima Yudhistira; I Putu Gde Sukaatmaja; Gde Indra Bhaskara (JURNAL MASTER PARIWISATA, 2020)
The opening of internet access to the public in 1991 pushed information into people's daily needs (Birger, 1997). Telephone manufacturers adopt the internet naturally in their products by launching mobile phones that have evolved into smartphones (Ira, 2012), allowing the internet to be accessed all the time. Economic aspects soon followed, assimilated in cyberspace into E-commerce that allows transactions of goods and services in cyberspace (Botha et at., 2008). In the world of tourism, the use of modern technology has become a necessity for many destinations to remain competitive and attractive to modern tourists. A form of new technology that is increasingly being used in public spaces is Augmented Reality (AR). Augmented reality technology allows users to receive information in the form of a display that contains a combination of real and virtual objects in the real world in real time. Technology is accessed via an app that is installed on a smartphone.This research aims to analyze the role of behavioral intention based on augmented reality applications in mediating the effect of perceived usefulness and perceived ease of use on the actual system use in bamboo bar Sanur. An augmented reality prototype application was developed specifically for this research. Quantification of human behavior is possible by combining the branch of psychology theory of planned behavior with e-commerce based mobile computing context (Imielinski & Korth, 1996). Keywords: behavioral intention, aplikasi, augmented reality, smartphone, e-commerce, TAM, Mobile computing Text